POTENSI EKSTRAK KENCUR (Kaemferia galanga L.) SEBAGAI IMUNOMODULATOR PADA TIKUS MODEL YANG TERINFEKSI Mycobacterium tuberculosis - Rosida, Kukuh Judy Handojo (JURNAL ILMIAH FARMASI AKADEMI FARMASI JEMBER, 2019)
Tuberculosis is an infectious disease caused by Mycobacterium tuberculosis. Tuberculosis can infect anyone in the patient's environment. Someone with good body immunity conditions will avoid tuberculosis. Increased immunity for tuberculosis sufferers is very important. The active substances contained in plants such as flavonoids and essential oils are important components in supporting the body's immunity. One plant that contains flavonoids and essential oils is kencur (Kaemferia galanga L.). This study aims to prove the potential of kencur extract as an immunomodulator in model rat infected with Mycobacterium tuberculosis. This study was a laboratory experiment using the kencur extract (EK) and samples of rats as a model. The sample used was 30 animals which were divided into 6 groups. Group 1 was a healthy animal (Normal). Groups 2, 3, 4 and 5 were treatment groups consisting of sick animals given placebo treatment (control), rifampicin (R), EK (Kencur Extract) and CRK (Mixture of Rifampicin and Kencur). Group 6 was a normal group given EK then infected with Mycobacterium tuberculosis (NK). Modeling was done by infecting experimental animals using Mycobacterium tuberculosis. The infection was 30 days and the treatment was 21 days. The parameters in this study were leukocytes and Laju Endap Darah (LED). The results of the kencur extract phytochemical screening study showed the presence of flavonoids. The results of the treatment showed that differences in the number of Leukocytes and LEDs between the control group and the treatment (sig 0.05). These results indicate that kencur extract has the potential as an immunomodulator.Keywords : Kaemferia galanga, Mycobacterium tuberculosis, imunomodulator